Editorial: ulcerative colitis submucosal fibrosis and inflammation: more than just strictures. Issue 7 (7th March 2018) - Magro, F.; Sousa, H. T.
Abstract : Linked Content This article is linked to Gordon et al paper. To view this article visithttps://doi.org/10.1111/apt.14526 .